Moderating Effects between Job Insecurity and Intention to Quit in Samples of Slovene and Austrian Workers - Jiménez, Paul; Milfelner, Borut; Šarotar Žižek, Simona; Dunkl, Anita (Naše gospodarstvo/Our economy, 2017)
Job insecurity is a serious stressor in the work environment, with negative work- related outcomes. The effects of job insecurity strongly depend on the country’s economic condition. The present study investigated the relationship among job insecurity, job satisfaction, and the intention to quit as well as possible mediating variables (resources/recovery and stress). The samples of 251 Slovene and 219 Austrian workers were analyzed. The data indicated that job insecurity is related to higher stress and intention to quit as well as to lower resources/recovery at the workplace. Stress is an important mediator in the relationship between resources/ recovery and job satisfaction as well as intention to quit. These relationships were found in both samples.